Processes, patterns, practices, and perspectives: What we talk about when we talk about “development” - Eldon, John (Cogent social sciences, 2017)
“Development” is a central term in an interdisciplinary discussion that brings together a diverse range of more conventional disciplines, including economics, politics, anthropology, and history. While this word is often used in highly specific ways within each of these contributing fields, the use can vary widely between them, leaving explicitly interdisciplinary discussions of “development” open to unnecessary semantic confusion. This paper breaks this multifaceted term down into the individual facets and constructs a descriptive typology that can be used to interpret individual uses in a text. This typology is then applied to four classic works that attack conventional understandings of “development” and a selection of articles in the journal World Development from 1973, 1993, and 2013. This analysis appears to document a maturation of interdisciplinary discussions of “development,” as evidenced through observation of increasing rigor, specificity, and a now nearly standard reliance of adjacent qualifying terms when “development” is used in an interdisciplinary text. However, it also finds that while these qualifiers are a semantic aid, they are not a satisfactory replacement for careful use of the term and clear presentation of the underlying ideas.